An evaluation of cervical cancer cases diagnosed at a South African colposcopy clinic - Mashayamombe, Rumbidzai Esinath (My University, 2019)
The public health impact of a screening programme introduced in SA in 2000 has not shown a reduction in the incidence of or deaths from cervical cancer. An important risk for death is the late stage at presentation. It may be that the women who present with cervical cancer within a screening programme present with early stages. This study aims to describe women with cervical cancer that were diagnosed within a screened population, who were referred to colposcopy from April 2003 to April 2016. Methods The CHBAH colposcopy clinic is a ‘see and treat clinic’ in a tertiary hospital in Soweto. Women are referred with abnormal cytology reports. A LLETZ is performed immediately when the colposcopic impression is greater than CIN1, if the colposcopy is inadequate, or if cytology and colposcopy are incongruent. This was a cross sectional study using data from a database and patient files. The following data was extracted: age, parity, contraception, HIV status, cytology, colposcopy, histology and staging. Results There were 174 women with cervical cancer. The median age was 45 years (IQR 38-55), the median parity was 3 (IQR 2-4) and 64 women (36.8%) were post-menopausal. Twenty eight (17.5%) women with a known contraceptive history were on hormonal contraception. Ninety four women (54.0%) were HIV positive. The median CD4 count was 329 cells/mm3 (IQR 177-502). iv The most frequent cytology results that women were referred with were “HSIL” (88 women, 50.6%), “malignant cells/suspected invasion” (30 women, 17.2%) and, “at least HSIL, cannot exclude invasion” (29 women, 16.7%). The colposcopic impressions were frank invasion (56 women, 32.2%), CIN3 (38 women, 21.8%), and microinvasion (33 women, 19.0%), CIN2 (21 women, 12.1%) and CIN1 (2 women, 1.2%). In 24 women (13.8%), the colposcopic findings were unknown or not recorded. The histological subtypes were squamous cell carcinoma (148 women, 85.1%), adenosquamous (9 women, 5.2%), adenocarcinoma (8 women, 4.6%), adenoid-basal (5 women, 2.9%), unspecified (2 women, 1.1%), and small cell neuroendocrine (1 woman, 0.6%). 1 women (0.6%) had a synchronous tumour. The presenting FIGO stage was known in 161 women. Stage 1A was diagnosed in 63 women (39.1%), 1B in 52 (32.3%), 2A in 5 (3.1%), 2B in 25 (15.5%), 3A in 0 women, 3B in 14 (8.7%), 4A in 1 woman (0.6%) and 4B in 1 woman (0.6%). Conclusion Roughly 75% of women in this study presented with FIGO stage 1a to 2a disease, which is associated with a 5 year survival of at least 68.8%. This contrasts to the late presentation which occurs in developing countries. There may be benefit, in that women diagnosed through a screening programme have earlier stage disease.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine (Obstetrics & Gynaecology) to the Faculty of Health Sciences, University of the Witwatersrand, 2019